Enzyme-assisted extraction of bioactive compounds from brown seaweeds and characterization - K. Habeebullah, Sabeena Farvin; Alagarsamy, Surendraraj; Sattari, Zainab; Al-Haddad, Sakinah; Fakhraldeen, Saja; Al-Ghunaim, Aws; Al-Yamani, Faiza (Journal of applied phycology, 2020)
Brown algae comprise the largest biomass producers in coastal waters and play important ecological roles. The complex nature of cell wall polysaccharides limits the extraction of bioactive compounds from these seaweeds. The aim of the study was to use enzyme-assisted extraction as a tool to release the bioactive compounds from seven brown seaweeds of Kuwait coast and characterization of the active extracts. The enzymatic extracts obtained by hydrolysing seaweeds with five carbohydrases and three proteases were screened for antioxidant and antimicrobial activity. Yield, total phenolics, and bioactivity were as a function of species difference in cell wall composition and specificity of the enzyme used. Among the six species of brown seaweeds studied, the enzymatic extracts obtained from Sargassum boveanum , Sargassum angustifolium , and Feldmannia irregularis showed high antioxidant activity in different assays. Though antimicrobial activities of the enzymatic extracts were low, Flavourzyme resulted in more number of seaweed extracts with antimicrobial activity against foodborne pathogens. In general, carbohydrases resulted in extracts with high radical scavenging activity whereas proteases resulted in extracts with high iron chelating activity. The extracts with highest antioxidant activity such as S. boveanum -Viscozyme and Alcalase extracts were further fractionated and characterized. The polyphenol and polysaccharide-rich fractions were responsible for the high radical scavenging and reducing power whereas the iron chelating activity and inhibition of lipid oxidation in liposome model system was mainly contributed by polysaccharide and protein-rich fractions. The results of study showed that enzyme-assisted extraction could be useful to make tailor-made seaweed extracts with specific bioactivity.